PERGESERAN FUNGSI KELUARGA BURUH MIGRAN PEREMPUAN DI DESA TELUKSAMAK KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Endah Utami; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The family is the smallest unit in society whose relationship is bound by marital relations in which the nuclear family is the father, mother and child who have their respective roles and functions. There are several functions of the family, namely the function of the economy and the function of affection or affection. To meet the economic needs that play a role in this case is the head of the family, but over time and the increasing number of needs this is not only done by the head of the family, but housewives have contributed to this. The topic of this research focus is, "Shifting Functions in Families of Female Migrant Workers in Teluksamak Village, Rangsang District, Meranti Islands Regency". The issues raised are, What is the process and mechanism for the departure of migrant workers and what is the form of shift in the migrant worker's family. The purpose of this study was to determine the process and mechanism for the departure of migrant workers and the form of shift in function within the migrant worker's family. The method used in this study is a qualitative research method. The research location is in Teluksamak Village, Rangsang Sub-district, Meranti Islands Regency. As for the informants in this study amounted to 5 people according to the specified criteria (propositive sampling). Data collection techniques used are observation, interviews, documentation and triangulation techniques. In general, the results of this research are housewives who work as migrant workers regularly enter Malaysia every month using a passport and ship transportation with a working time of 24-27 days per month. The shift that occurs is the exchange of roles between husband and wife in a household where the wife earns a living and the husband takes care of the children and other household needs. Keywords: Shift function, family